Intermittent lower bound on quantum diffusion - Guarneri, Italo; Schulz-Baldes, Hermann (Letters in Mathematical Physics, 1999)
An intermittent lower bound on quantum diffusion is proven in presence of a multifractal spectral measure.
UnivIS-Import:2015-03-05:Pub.1999.nat.dma.pma22.interm
Keywords: Multifractal measures; Quantum diffusion